Enhancing the Paikem Learning Model's Applicability: The Clinical Supervision Model - Purba, Saut; Parhusip, Akdel (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine the increase in the ability of class teachers to implement the PAIKEM learning model through the application of clinical supervision with a collaborative approach at SDS Santa Lucia Sei Rotan. A sample of 10 people was determined based on a purposive sampling technique. The research was conducted in two cycles, each consisting of four stages: planning, implementing activities, observing, and reflecting. Data collection through interviews, observation, and documentation. The study's results concluded: (1) In the pre-cycle, teachers still needed to implement the PAIKEM learning model. (2) In the first cycle, the teacher's ability score to apply the PAIKEM learning model = 52.22 (very low). In the second cycle, the teacher's ability increased significantly, namely 95.46 (very good). (3) Student activity in the first cycle average score = 65 (poor category). There was a fairly high increase in the second cycle, with an average score = of 91.67 (very good). The findings of this study, through the application of clinical supervision with a collaborative approach, can improve the teaching abilities of class teachers with the PAIKEM learning model.